10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
Ultrasound examinations have the potential to transmit infections between individuals. The risk can be reduced by following certain well-described procedures to clean and disinfect ultrasound transducers between examinations. However, surveys have shown widespread lapses in the cleaning and disinfection of transducers and other equipment. In 2020, the Society for Maternal-Fetal Medicine (SMFM) published a Patient Safety Guideline focused on reducing the risk of transmitting infection in transvaginal examinations, with emphasis on selection of high-level disinfectants with proven efficacy against human papillomavirus (HPV), choice of transducer covers with documented low leakage rates, and cautions regarding multiuse containers of coupling gel. In this article, SMFM presents updated guidelines with an expanded scope that includes transabdominal examinations and ultrasound-guided percutaneous and intraoperative procedures. Other updates include a list of newer high-level disinfection systems and citation of recent literature on virucidal efficacy of ortho-phthalaldehyde against HPV. The guidelines are based on the Spaulding classification of infection risk and are aligned with recommendations from the American Institute of Ultrasound in Medicine, the Centers for Disease Control and Prevention, and the US Food and Drug Administration. This Special Statement replaces Society for Maternal-Fetal Medicine Special Statement: Reducing the risk of transmitting infection by transvaginal ultrasound examination, 2020.